(untitled) (CIPEEX, 2025)
Objective: To determine the relationship between nasal septal deviation (NSD) and increased sinus mucosal thickness and inflammatory changes in the maxillary sinus resulting from periapical infections, using dynamic navigation with new cone beam computed tomography software. Material and method: The study sample consisted of 200 cone-beam computed tomography scans of patients of both sexes. The inclusion criteria were images involving those who had the nasal septum within the field of view. To determine the relationship between nasal septum deviation and sinus mucosa thickening, the types of nasal septum deviation were correlated. Results: The evaluation of the relationship between nasal septum deviation and increased mucosal thickness showed that 61% had no changes in the mucosa, of which 32.50% had no DSN, and 11.50% had Type III deviation. The relationship between nasal septum deviation and the maxillary sinus showed that 61% had no changes in the maxillary sinus, and of this total, 32.50% did not have DSN. In the relationship between nasal septum deviation and periapical infection, 44.50% of individuals did not present infection and, of these, 21.00% did not have DSN and 18.90% presented Type III deviation. Conclusion: In the evaluation of the relationship between nasal septum deviation and increased mucosal thickness, it was found that 61% of individuals did not present changes in the mucosa, however 32.5% presented type III DSN. In the relationship between DSN and periapical infection, 44.5% did not present infection and of these, 21% did not present deviation.